2014
DOI: 10.1080/09669582.2014.986490
|View full text |Cite
|
Sign up to set email alerts
|

Using Ostrom's common-pool resource theory to build toward an integrated ecosystem-based sustainable cetacean tourism system in Hawai`i

Abstract: and Clyde Streets, Dunedin 9054, New Zealand This paper explores the suitability of community-based conservation measures to complement a proposed command-and-control approach for two multi-user bays with spinner dolphins in Hawai`i, USA, which have considerable dolphin watching tourist activities and human-dolphin interactions. The paper uses Ostrom's common-pool resource theory as an analytical lens, with an assessment of the attributes of the resource and the user(s) to explore questions of governance and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
38
0
9

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 41 publications
(48 citation statements)
references
References 37 publications
1
38
0
9
Order By: Relevance
“…Bay 2 is a popular coral reef snorkeling destination and people visit this bay for purposes other than interacting with the dolphins. However, human activities in Bay 1 are dolphin-centric with significantly more human activity occurring when dolphins are present (Heenehan et al, 2014). This supports our conclusion that although the activity levels may be high, tourism that is not dolphin-centric (Bay 2) appears less disruptive for the dolphins in the bay than tourism that it dolphin centric (Bay 1).…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…Bay 2 is a popular coral reef snorkeling destination and people visit this bay for purposes other than interacting with the dolphins. However, human activities in Bay 1 are dolphin-centric with significantly more human activity occurring when dolphins are present (Heenehan et al, 2014). This supports our conclusion that although the activity levels may be high, tourism that is not dolphin-centric (Bay 2) appears less disruptive for the dolphins in the bay than tourism that it dolphin centric (Bay 1).…”
Section: Discussionsupporting
confidence: 80%
“…A major difference between Bay 1 and Bay 2 is the focus of human activity in the bays. Heenehan et al (2014) showed that in Bay 2 there was no significant difference in vessels, swimmer/snorkelers or kayaks when dolphins were present versus when they were absent indicating the activity in Bay 2 is not dolphin-centric. Bay 2 is a popular coral reef snorkeling destination and people visit this bay for purposes other than interacting with the dolphins.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Clearly, the need for future estimates and evaluation of change in the Hawaii Island spinner dolphin population size is a priority for managers because of the small population size (Tyne et al 2014), its genetic isolation (Andrews et al 2010) and the use of the four bays important for resting spinner dolphins , where the dolphins encounter significant numbers of human activities on a daily basis (Heenehan et al 2015) .…”
Section: Monitoring Changes In Dolphin Abundance Over Timementioning
confidence: 99%
“…They forage cooperatively offshore at night, and return to sheltered bays to socialise and rest during the day (Norris and Dohl 1980;Norris et al 1994;Benoit-Bird and Au 2009;Tyne et al 2015) during which time the bays are also used extensively by people for tourism, recreational and subsistence purposes (Heenehan et al 2015). Some of these activities, in particular nature-based tourism, engage in repeated, close-up encounters with dolphins on a daily basis (Heenehan et al 2015). These close-up encounters may have negative consequences for spinner dolphins, which is a major concern for managing the population.…”
Section: Introductionmentioning
confidence: 99%